MAVEN mission perspectives and approaches to inclusion - Curry, S. M. (Frontiers in Astronomy and Space Sciences, 2023)
The Mars Atmosphere and Volatile Evolution mission (MAVEN) is a NASA spacecraft that has been orbiting Mars since 2014. The MAVEN team has established a current set of best practices to strengthen Diversity, Equity, Inclusion, and Accessibility (DEIA) initiatives; there are numerous axes of diversity, and this paper does not focus on one specific aspect of diversity but rather focuses on mission-specific approaches to inclusion. We present the past and present approaches as well as future initiatives and areas of improvement to continuing our efforts towards maximizing inclusion and engagement on the MAVEN team and its working environment. The approaches presented in this paper are applicable to the space physics and planetary science communities, as well as any large-scale science or mission teams.